Kajian Pemikiran Pendidikan Islam dalam Perspektif Literatur Klasik: Studi atas Pemikiran Ibnu Khaldun - Putri, Widia; Sujarwo, Sujarwo (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
Abstract This study aims to analyze Ibn Khaldun's thoughts on education which include biography, concept of education, method of education, curriculum of education, and purpose of education. This study uses a qualitative approach with the type of Library Research study then traces and analyzes sources related to education then collected and concluded. The results of this study are that Ibn Khaldun believes that education is the core of human existence on this earth. In the discussion of the curriculum, Ibn Khaldun explains that the curriculum is a program of education that involves objectives, content, teaching methods and assessments. Ibn Khaldun also emphasized the importance of using creative teaching methods in order to get a positive response from students. He also advised not to use violent tactics because it has a significant impact on students, it can make students lazy. Learning the Qur'an must also be emphasized after students are able to reach a level of ability in thinking, because the Qur'an can strengthen faith in Allah and behave well as creatures of Allah. Keywords: Ibn Khaldun's Thoughts, Islamic Education, Educators, Students